Comparative Evaluation of Two Types of Immediately Loaded Implants Using Biomechanical and Histomorphometric Tests: An Animal Case Study. (18th July 2012) - Rismanchian, Mansour; Movahedian, Bijan; Khalighinejad, Navid; Badrian, Hamid; Mohammad Razavi, Sayed; Nekouie, Afsaneh
Abstract : Introduction. In order to minimize the required time to regain esthetic and function, immediately loaded implants were suggested. The aim of this study was to comparatively evaluate the Nisastan and XIve implants using biomechanical and histomorphometric tests. Materials and Methods. In this experimental study, 6 Nisastan one-piece immediately loaded screw type implant (OPILS) and 6 Xive implants with 3.4 mm diameter and 11 mm long were used. The implants were immediately loaded with temporary coating. After three months, the torque required to break bone-implant contact was measured and was recorded. All implants were extracted with surrounding bone and histologically were evaluated. The data were inputted into the SPSS 11.5 to run student T-test statistical analyses (α = 0.05 ). Results. The success rates of both types of implants was 100%, and none of them failed due to mobility or bone loss. The mean removal torque value (RTV) was 142.08 and 40 N/Cm for Xive and Nisastan implants, respectively, and their RTVs showed a significant difference between two mentioned implants (P = 0.004 ). None of the histomorphometric values showed significant differences between the two implants (P > 0.05 ). Discussion. both systems have the capability to induce osseointegration under immediate loads but that Xive implants showed higher capability for bone contact.